Can Albania and Greece go Toward a Conflict for the Fulfillment of their Interests? (Liberalism vs. Realism) - Borakaj, Daniel; Gjergji, Lorena (Richtmann Publishing, 2012)
Liberalism can describe the Albanian – Greek relations, more than realism does. This paper is a confrontation of the gametheory with sum zero and the game theory win – win. The assessment is that Liberalism gives a clear and fair view of the Albanian –Greek relations adding other elements left aside by Realism. 1) Liberalism studies plurality of actors that have influenced the Albanian –Greek relations. 2) This relation is characterized not only by individual interests of states, but also by some mutual interests. 3) Force issubstituted by interaction and cooperation. Based on this logic, a projected conflict in the future of the Albanian – Greek relation can notbe perceptible and it is unlikely to happen. The conclusion of this paper may be used to foresee other relations of Albania with neighborcountries.